The application of tea tree essential oil in dentistry - Marković D.; Mirković B.; Jovanović T.; Knežević A.; Nastovski T. (Serbian Medical Society - Dental Section, Belgrade, 2007)
Essential oils are widely used in medicine, dentistry and cosmetology as flavour and odour corrigents in various substances for oral hygiene. The aim of this study was to present comprehensively the possibilities for application of Melaleuca Alternifolia essential oil in dentistry based on the analysis of contemporary scientific and professional publications. The application of Tea tree essential oil in the treatment of periodontal, fungal and viral diseases is very efficient. The study of antimicrobial potential of ten different essential oils confirmed the efficiency of Tea tree oil against numerous Gram+ and Gram- bacteria. In vitro studies of bacteriostatic, bactericidal and fungicidal effect of Tea tree oil solution against ten different microorganisms confirmed sensitivity of the following microorganisms: Actinobacillus actinomycetemcomitans, Fusobacterium nucleatum and Porphyromonas gingivalis, and slightly weaker effect against Streptococcus Mutans and Prevotella intermedia. Tea tree is very effective in the treatment of various diseases and is an introduction and momentum for the application of plant substances in the treatment of numerous diseases in dentistry. .